2023
DOI: 10.3390/polym15040917
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lavender-Oil Microcapsules to Functionalized PET Fibers

Abstract: Surface treatments for textile substrates have received significant attention from researchers around the world. Ozone and plasma treatments trigger a series of surface alterations in textile substrates that can improve the anchoring of other molecules or particles on these substrates. This work aims to evaluate the effect of ozone and plasma treatments on the impregnation of polymeric microcapsules containing lavender oil in polyester fabrics (PES). Microcapsules with walls of chitosan and gum arabic were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The TGA outcome showed that the initial mass loss occurred at 280 o C. Furthermore, the greatest rate of weight loss was noted between 281-394°C, which is related to the cellulose's degradation. The encapsulated cotton fabric's (C1, C5, C7, C8, C13) TG curve showed a lower temperature of disintegration, with the greatest rate of weight decrease occurring between 234°C and 394°C (Valle et al 2023). The decomposition temperature and mass loss are shown in Fig.…”
Section: 11(tga) Thermogravimetric Analysismentioning
confidence: 95%
“…The TGA outcome showed that the initial mass loss occurred at 280 o C. Furthermore, the greatest rate of weight loss was noted between 281-394°C, which is related to the cellulose's degradation. The encapsulated cotton fabric's (C1, C5, C7, C8, C13) TG curve showed a lower temperature of disintegration, with the greatest rate of weight decrease occurring between 234°C and 394°C (Valle et al 2023). The decomposition temperature and mass loss are shown in Fig.…”
Section: 11(tga) Thermogravimetric Analysismentioning
confidence: 95%